The feasibility of integrating digital mobile devices into secondary education in South Africa; particularly in the area of learner social support - Reddy, Ashley Corneil (My University, 2017)
In this study, the affordances of Digital Mobile Devices for educational purposes was explored, with an emphasis on determining the feasibility of integrating Digital Mobile Devices into secondary education in South Africa; particularly in the area of Learner Social Support. An empirical, qualitative research approach was adopted, where a questionnaire was administered for the collection of data, and this data was analysed for possible trends. The experiences and perceptions of both educators and learners at both schools have been detailed. It was ascertained through both the literature and the analysis of data that Digital Mobile Devices are advantageous, and ubiquitously owned and used by both educators and learners. This exposed the fallacy of the existence of a digital divide on the basis of access to ICTs. Conclusions have been drawn as to the feasibility of integrating Digital Mobile Devices into secondary education in South Africa, and recommendations have been made for further investigation into the non-adoption of Digital Mobile Devices into secondary education in South Africa.
A research report submitted to the School of Education, Faculty of Humanities, University of the Witwatersrand, Johannesburg, in partial fulfillment of the requirements for the degree of Masters in Education. Johannesburg 2017.
Keywords: Educational technology--Study and teaching (Secondary)--South Africa; Education, Secondary--South Africa--Computer-assisted instruction